Surgical outcomes and feasibility of transvaginal sacrospinous ligament fixation through anterior approach for women with pelvic organ prolapse - Mohini Agrawal; Rajesh Kumari; J B Sharma; N Nisha; Deoghare Manasi; Neerja Bhatla (Journal of Mid-Life Health, 2023)
Introduction: Supporting vaginal vault or apex is a central component of primary therapy and to prevent recurrence of prolapse. This study aims to review the surgical outcomes and feasibility of the anterior approach following both sacrospinous fixation (SSF) and sacrospinous hysteropexy (SSHP) in a single center over a specific period. And also to review its impact on quality of life. Materials and Methods: This was a retrospective study that included all women who underwent unilateral SSF or SSHP through anterior approach for pelvic organ prolapse (POP) from May 2021 to May 2023 after institutional ethical approval for the study. The anterior approach was undertaken in 47 patients which were included in final review. A retrospective case note review to assess urinary symptoms was undertaken at baseline and 3 months by urinary distress inventory 6 score. The main outcome measure was recurrence of prolapse, predominant compartment for prolapse, presenting complaints, concomitant surgeries performed, and associated urinary complaints. Results: The mean age was 56.17 ± 11.95 years and the average body mass index was 26.12 ± 3.11 kg/m2. Except for 4 cases of SSHP, remaining women were postmenopausal at the time of surgery. Ten women presented with urinary complaints as their chief complaint. On examination, POP Quantification evaluation, 35 cases have Ba as leading point, 10 have Ap as their leading point and in two cases C was the leading point. Conclusion: Anterior unilateral sacrospinous ligament fixation is a safe, effective strategy to treat POP and other concomitant surgery can also be well combined with it.